Leliefontein : structure and decline of a Coloured mission community 1870-1913 - Price, Melanie Jane (Department of Historical Studies, 2016)
Leliefontein is a Coloured Reserve in the magisterial district of Namaqualand. There are five Coloured Reserves in Namaqualand: Leliefontein, Komaggas, Steinkopf, Concordia and Richtersveld. All these Reserves owe their existence to missionary influence. Leliefontein is the most southerly of the reserves, and the only reserve where mission work is controlled by the Methodist Church. The missions to the North are under the guidance the Dutch Reformed Church. Leliefontein covers an area of 75, 000 acres. To the North-east lies Bushmanland, to the West stretches the vast coastal plain. Leliefontein lies roughly between the towns of Garies and Kamieskroon. The heart of Leliefontein lies in the Kamiesberg range of mountains and much of the Reserve is mountainous and hilly.